Significant Association of CXCL12 rs1746048 with LDL-C Level in Intracranial Aneurysms - Zhang, Junjun; Shen, Haoyuan; Wang, Mengjun; Nie, Sheng; Wu, Xizheng; Huang, Yi; Gao, Xiang (Current Neurovascular Research, 2018)
Background: C-X-C motif chemokine ligand 12 (CXCL12) may play an important role in the development of Intracranial Aneurysm (IA). Objective: The goal of this study was to explore the association between CXCL12 rs1746048 genotypes and circulating lipid concentrations along with the risk of IA. Methods: A total of 256 IA patients and 361 healthy volunteers were included in the case-control study. The genotypes of CXCL12 rs1746048 were detected by Melting Temperature shift (Tmshift) Polymerase Chain Reaction (PCR). Results: Significant higher levels were seen in Total Cholesterol (TC) (padjusted < 0.001), Highdensity Lipoprotein Cholesterol (HDL-C) (padjusted < 0.001), Low-density Lipoprotein Cholesterol (LDL-C) (padjusted < 0.001), Apolipoprotein A-I (ApoA-I) (padjusted = 0.040), and Apolipoprotein B (ApoB) (padjusted < 0.001) in IAs compared with controls. CXCL12 rs1746048 T allele frequency showed significant association with the risk of IA in the female group aged 65 or above (p = 0.019, Odds Ratio (OR) = 2.15, 95% confidence interval (95%CI) = 1.13 – 4.11, power = 64.8%). Moreover, CXCL12 rs1746048 was likely to be a risk variant of IA under the recessive model in females older than 65 years. (p = 0.030, OR = 3.77, 95%CI = 1.08 – 13.12, power = 81.8%). Additionally, we also found that the levels of LDL-C were significantly different among three genotypes (CC vs. CT vs. TT = 2.75±0.73 vs. 3.03±0.89 vs. 2.82±0.72, p = 0.035) in IA patients. Conclusion: Our results suggest that CXCL12 rs1746048 is significantly associated with IA risk in Han Chinese females aged 65 years and older. Additionally, the genotypes of CXCL12 rs1746048 may affect the LDL-C concentrations in IA patients.
Keywords: CXCL12